2018
DOI: 10.1093/annonc/mdy074
|View full text |Cite
|
Sign up to set email alerts
|

Combined pathologic‐genomic algorithm for early-stage breast cancer improves cost-effective use of the 21-gene recurrence score assay

Abstract: AAMC model is capable of predicting 5-year recurrences in high- and low-risk groups similar to RS. Further, using the P-G algorithm, reserving RS for AAMC intermediate cases, results in larger low- and high-risk groups with similar prognostic accuracy. Thus, the P-G algorithm reliably identifies a significant portion of patients unlikely to benefit from RS assay and with improved ability to categorize risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A multivariate logistic regression analysis of an updated nomogram revealed that all five clinicopathologic variables were significant predictors for a low-risk or a high-risk ODXRS test results with grade and PR status carrying the highest impact. Grade and PR status were also shown by Gage et al [26,34] and Huang et al [35] as significant predictors of ODXRS test results in different ODX prediction models.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A multivariate logistic regression analysis of an updated nomogram revealed that all five clinicopathologic variables were significant predictors for a low-risk or a high-risk ODXRS test results with grade and PR status carrying the highest impact. Grade and PR status were also shown by Gage et al [26,34] and Huang et al [35] as significant predictors of ODXRS test results in different ODX prediction models.…”
Section: Discussionmentioning
confidence: 61%
“…Recently published studies implied that ordering of ODX test for every eligible ERþ/HER2-negative/lymph node-negative female patients with invasive breast carcinoma might not contribute to clinical management decisions. Some of these studies suggested that analysis of some of the clinicopathologic data available from pathology reports may select patients for which ODX test results were highly predictable and, therefore, the test could be safely and appropriately avoided [33,34]. We previously developed a "user friendly" nomogram/calculator [14] as a surrogate prediction model for the ODX score.…”
Section: Discussionmentioning
confidence: 99%
“…On another hand, cost-effectiveness analysis demonstrated that the 21-gene RS testing was only associated with lower cost in patients with clinical high-risk [14,15]. Thus, a surrogate for the 21-gene RS testing is needed for those who have no access to this assay, as well as to relieve the heavy financial burden of patients for whom the testing is not cost-efficient [16]. The NSABP B-20 retrospectively validated that patients with RS > 30 could have better distant recurrence-free survival if they received chemotherapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is currently recommended by NICE with the use of PREDICT or NPI. Gage et al [ 68 ] analysed information about 1268 breast cancer patients from the University of Texas MD Anderson Cancer Center database. The mean age of the group was 54.8 years.…”
Section: Discussionmentioning
confidence: 99%